Monitoring antimicrobial cross‐resistance with cross‐resistance rate correlation diagrams: Changes in antibiotic susceptibility of Pseudomonas aeruginosa due to hospital relocation. (28th October 2020) - Hatsuda, Yasutoshi; Ishizaka, Toshihiko; Koizumi, Naonori; Yasui, Yukako; Saito, Takako; Omotani, Sachiko; Maki, Syou; Teramachi, Hitomi; Myotoku, Michiaki
Abstract: What is known and Objective: Though most medical institutions calculate antimicrobial susceptibility and resistance rates of microbes isolated at their own facility as part of their efforts to promote the proper use of antibiotics, very few, if any, regularly monitor cross‐resistance rates between antimicrobial agents. The authors have devised a tool in the form of a cross‐resistance rate correlation diagram (CRR diagram) that allows easy identification of increases or decreases in, or changes in the pattern of, antimicrobial cross‐resistance. The objective was to perform an analysis by CRR diagrams of the effect of relocation to a newly built facility on antimicrobial resistance and cross‐resistance rates at a medical facility. Methods: The Sakai City Medical Center relocated in July 2015 to a newly built facility located in a different primary medical care zone 3.5 km away. Based on the drug susceptibility test data compiled at the Sakai City Medical Center, resistance and cross‐resistance rates of Pseudomonas aeruginosa before and after the relocation of the hospital facility were calculated, and the rates were assessed using CRR diagrams. Results and discussion: It was possible to confirm the effect of hospital relocation on antibiotic susceptibility of P aeruginosa in terms of changes in resistance and cross‐resistance rates. The effect of the facility's relocation on cross‐resistance rates was particularly notable with respect to β‐lactam antibiotics: cross‐resistance rates among β‐lactams decreased substantially, represented as a large wedge‐shaped change towards the origin on the CRR diagram. Rates of cross‐resistance between classes of antibiotics with a different mechanism of antibiotic action changed little. What is new and conclusion: Including cross‐resistance rates in the routine monitoring of resistance and susceptibility rates practiced by a medical institution can provide a comprehensive insight into the dynamics of bacterial flora in the facility. CRR diagrams, which allow visualization of the status and changes in cross‐resistance, not only provide a new perspective for clinicians, but they also contribute to the proper use of antibiotics and serve as a tool in the education of healthcare professionals and students about antibiotic resistance. Abstract : CRR diagram gives an overview of cross‐resistance between antimicrobial agents.